THE USE OF GOOGLE VOICE SEARCH IN IMPROVING THE STUDENTS’ PRONUNCIATION ACCURACY - Fidaniar Tiarsiwi; Martriwati (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
The use of mobile technology for everyone is like a necessity in daily life. No one can ignore the impact of mobile technology especially from android mobile system that led the progression of technology todays. However, this technology development can be utilized by language learners to increase and encourage them in mastering the English language use. They can utilize the application inside the android system in improving pronunciation accuracy. Furthermore, it can help teachers to teach their learners in using English language spoken. Everyone knows that learning pronunciation needs time to take some practices. The writer initiated the application of learning English pronunciation by using a default application inside android system. The application calls as Google Voice Search. It can be used as learning strategy to improve the accuracy for learner and to be aware about the mistake which has been made by them. This Google voice Search system can be used as self-evaluation in pronouncing English language. This study investigated the first semester students of English Department in Jakarta. The writer designed the study as learning strategy to help learners aware about their mistake in pronouncing English language. The use of android mobile phone is shown the progression of most 72% learners’ pronunciation growing better and it improved learners’ confidence in using English orally. They also stated that they really like this application because it led them to be more technology savvy. It can facilitate the learners in pronouncing English accurately when they use in spoken English. Keywords: Android, Application, Pronunciation, Google Search Voice